Community perceptions of yellow fever and its treatment practices in regions with reported outbreaks in Uganda: A qualitative study. - Lena Huebl; Aloysious Nnyombi; Patricia Apoko; Denis Okello; Eddy Walakira; Ruth Kutalek (PLoS Neglected Tropical Diseases, 2025)
Background Yellow fever (YF), a mosquito-borne viral hemorrhagic fever, is endemic to Uganda and has caused numerous outbreaks in recent years. This study explored local perceptions of YF outbreaks among vulnerable groups in Uganda to inform future public health campaigns. Methodology A qualitative study examined community perceptions of YF and its treatment practices. Data were collected in six districts where YF outbreaks were reported in 2010 and 2016. A total of 76 individuals participated, comprising 43 semi-structured interviews, 10 expert interviews, and 4 focus group discussions, including vulnerable groups of older adults ≥ 65 years and pregnant women. Data were analyzed using grounded theory. Principal findings Participants often recognized jaundice but did not distinguish YF from other causes of jaundice, such as newborn jaundice, severe malaria or hepatitis. Nevertheless, participants still considered YF a deadly disease. It was perceived to be transmitted through multiple pathways, including mosquito bites, airborne transmission, close contact with sick individuals, sexual intercourse, vertical transmission during pregnancy, poor hygiene, and certain foods. Treatments ranged from herbal remedies to visiting health centers. Several YF survivors shared first-hand experience, often relying on traditional medicine due to limited access to health facilities, diagnostic options, and no specific treatment for YF. In remote areas, participants often did not know the cause of the outbreak, as awareness campaigns focused on symptoms, prevention, and mass vaccination. Conclusions/significance If YF is not seen as a distinct disease entity, implementing diagnostic and preventive measures may be impeded. Moreover, failure to diagnose YF in clinical settings can hamper timely outbreak response. We recommend strengthening health literacy through health education and public participation in vulnerable communities with programs tailored to local needs, given that other infectious diseases are prevalent in the region. Furthermore, we propose that access to diagnostic testing for YF may be enhanced.